Recovery and Modification of Waste Tire Particles and Their Use as Reinforcements of Concrete - Eduardo Sadot Herrera-Sosa; Gonzalo Martínez-Barrera; Carlos Barrera-Díaz; Epifanio Cruz-Zaragoza; Fernando Ureña-Núñez (International Journal of Polymer Science)
Environmental pollution caused by solid wastes is increasing in the last decades; one of these is referred to automotive tires, which are recycled by different methods, including mechanical grinding. One of the most recurrent applications is to use recycled particles as fillers in building materials, as hydraulic concrete. Nevertheless, detrimental values on the mechanical properties are obtained when they are added. For solving these problems, in this work, a novel proposal is to modify the physicochemical properties of the waste automotive tire particles, previously obtained by grinding process, by using gamma irradiation in order to use them as reinforcements of hydraulic concrete. The results show that improvements on the mechanical properties depend of gamma irradiation as well as concentration and size of waste tire particles. Moreover, SEM images are related to mechanical properties; for instance, rough surface of the tire particles changes when applying irradiation; more smooth surfaces are created, due to the cross-linking of polymer chains. Nevertheless, for higher doses, cracks are observed which are produced by scission of the polymer chains.